BERPIKIR REFLEKTIF SISWA DALAM PEMECAHAN MASALAH MATEMATIS DITINJAU DARI GAYA KOGNITIF - Nur Mafaza, Azkia; Eko Subekti, Fitrianto (Department of Mathematics Education, Universitas Kuningan, 2024)
This research aims to analyze the ability of reflective thinking in mathematical problem solving among 9th-grade students of SMP Negeri 3 Tanjung, focusing on curved surface solids from the perspective of cognitive styles. The sample selection was carried out using a purposive sampling technique, resulting in 6 participants, consisting of 3 students with a field-dependent cognitive style and 3 students with a field-independent cognitive style. Data collection techniques employed in this study include the GEFT test, a test of reflective thinking ability in mathematical problem solving, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, involving data reduction, data presentation, and conclusion. The results of this study indicate that among the four indicators of reflective thinking ability in mathematical problem solving, specifically in the elaborating stage, students with a field-dependent cognitive style have not fully grasped the ability to plan and execute solutions. They struggle to comprehend more complex problems presented in narrative form, leading to difficulties understanding the concepts and executing the solution process. Conversely, students with a field-independent cognitive style have successfully fulfilled all four indicators across the three stages of reflective thinking ability. They tackle problems methodically and accurately, following planned steps following pre-established concepts.